MINECRAFT EDUCATION FOR IMPROVING ACADEMIC PERFORMANCE: A COMPARATIVE STUDY IN PRIMARY EDUCATION - Juan Carlos Piñero,; Lucena, Francisco Javier Hinojo; Rodríguez, Jose María Romero; Victoria-Maldonado, Juan José (Revista Conhecimento Online: Diversidade e Inclusão Social, 2025)
Minecraft Education is a popular construction game that immerses students in interactive virtual environments. By using this tool, students can engage in various learning activities and develop collaborative and problem-solving skills. This study aimed to determine whether incorporating Minecraft Education into the teaching of fractions improved students' learning and grades. A quasi-experimental design was employed, with a control group and an experimental group, involving two groups of primary school students (n = 25). The control group received a fraction learning session using traditional teaching methods, while the experimental group received the same session using Minecraft Education as an educational tool. The results indicated that the experimental group performed better academically on the topic of fractions compared to the control group. Furthermore, students using Minecraft Education demonstrated higher levels of engagement and achieved better marks during the session. The interactive and visual nature of Minecraft Education allowed students to explore abstract fraction concepts in a more tangible and practical way, facilitating deeper and more lasting understanding.